엔터테인먼트 기업의 기업가적 지향성과 기업성과의 관계에 관한 연구 - 김동하(Dong-Ha Kim); 유건재(Gun-Jea Yu); 이광철(Kwang-Chul Lee) (한국콘텐츠학회논문지, 2018)
This study analyzed how the entrepreneurial orientation of Korean CEO influenced to the performance of companies in entertainment business. The research verified the direct influence that the entrepreneurial orientation of entertainment business affected the companies' performance, and examined the diversity of TMT and the control effect of corporate governance. This study contributed to previous researches in two ways. The first, the study verified the concept of entrepreneurial orientation on entertainment business which was only focused on manufacturing or IT industry although the entrepreneurial orientation received attention as a significant research issue on middle and small venture businesses. Second, the research also verified the characteristics of CEO and executives bringing the concept of TMT's diversity in entertainment companies which were dependent on person's capacity. As a result of the research, the entrepreneurial orientation (innovation, proactiveness, risk-taking) of entertainment entrepreneurs led to a positive effect on financial performance. The research showed that the more TMT was diverse or ownership oriented management, the more broadened the positive effects. 본 연구는 한국 엔터테인먼트 기업 경영자들이 지닌 '기업가적 지향성'(EO, Entrepreneurial Orientation)이 기업의 성과에 어떠한 영향을 미치는지를 분석하였다. 엔터레인먼트 기업의 기업가적 지향성이 기업 성과에 미치는 직접적인 영향을 검증하고, 최고경영층(TMT: Top Management Team)의 다양성과, 지배구조 유형의 조절효과를 알아보았다. 본 연구는 기존 연구에 두 가지 면에서 기여를 한다. 첫째, 중소벤처기업 연구의 중요한 이슈로 주목을 받고 있지만 주로 제조, IT기업 위주의 연구에 머물러 있던 기업가적 지향성의 개념을 성장산업인 엔터테인먼트 산업에서 검증하였다. 둘째, 사람의 역량이 큰 역할을 하는 엔터테인먼트 기업 경영자와 임원들의 특성을 TMT의 다양성이라는 개념을 도입해 검증하였다.연구 결과 엔터네인먼트 기업가들이 지닌 기업가적 지향성(혁신성, 진취성, 위험감수성)은 기업의 재무적 성과에 긍정적인 영향을 미쳤다. TMT가 다양할수록, 대주주 영향력이 강한 소유 직접경영일수록 긍정적인 영향력은 확대되는 것으로 나타났다.